2011
DOI: 10.5897/ajb11.2463
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and pomological characteristics of fig (Ficus carica L.) cultivars from Varamin, Iran

Abstract: In this study, physical characteristics and quality parameters of some local cultivars of fig (Ficus carica L.) grown in Varamin, Iran were determined. The main cultivars grown in Varamin were Bidaneh, Paizeh, Zard, Siah bolol riz, Siah zoodras, Siah diras, Morabaii, Hallavi riz and Hallavi dourosht. In the pomological characteristics, fresh fruit weight ranged from 8.0 to 43.5 g. Fruit diameter ranged from 21 to 45 mm, the total amount of sugar ranged from 9.8 to 18.9%, the amount of total soluble solid range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…The length of the fruits changed according to handling practices; in this research, the length ranged from 6.57 cm to 7.53 cm, compared with those reported by Karadeniz (2008) who found that the genotypes of the Black Sea region, in Turkey, had a length of 3.32 to 6.05 cm. Regarding the diameter of the fruits, the values were constant, about 4.4 cm, compared with the values reported by Darjazi (2011), who found fruits with an equatorial diameter of 2.1 to 4.5 cm.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The length of the fruits changed according to handling practices; in this research, the length ranged from 6.57 cm to 7.53 cm, compared with those reported by Karadeniz (2008) who found that the genotypes of the Black Sea region, in Turkey, had a length of 3.32 to 6.05 cm. Regarding the diameter of the fruits, the values were constant, about 4.4 cm, compared with the values reported by Darjazi (2011), who found fruits with an equatorial diameter of 2.1 to 4.5 cm.…”
Section: Discussioncontrasting
confidence: 43%
“…In Iran, Darjazi (2011) also described the phenotypic diversity of fresh fruit weighing from 8.0 to 43.5 g. and in Turkey, Karadeniz (2008) reported fruits weighing between 22.21 and 77.40 g. However, they were inferior when compared with those obtained by Gaaliche et al (2011), in Tunisia, of 102 and 112 g with Zidi and Bouhouli cultivars, respectively. About the total soluble solids ranging from 17.79 to 21.14%, the results coincided with those found by Gaaliche et al (2011) of 20.3%, and were within the range reported by Karadeniz (2008) from 10.34 to 20.5% and Darjazi (2011) from 13.13 to 28.5%. However, they were closer to those by Sánchez et al (2003) who reported a range between 19.7 and 24.7% in Spain.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, several studies have reported on the healthpromoting potential of brebas and figs due to the presence of high concentrations of polyphenols, specifically in dried figs [9]. These nutritional and functional characteristics are closely related to fruit quality and are usually influenced by genotype and ripening stage, as well as by environmental conditions and orchard management practices [5,10,11]. The Scientific and Technological Research Center of Extremadura (CICYTEX-"Finca La Orden" in Guadajira (Badajoz)) is the national fig reference center in Spain, with over 200 different varieties that can be consumed either fresh or dried.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the most discriminating traits is especially important for all the crops (Khadivi-Khub and Anjam, 2014). Morphological descriptors remain the first step in the conservation process of the plants (Podgornik et al, 2010) and the most suitable tool for genetic diversity (Darjazi, 2011). With the above background and scope a study was conducted to characterize 12 coloured rice advanced cultures developed at ARS, Bapatla.…”
Section: Introductionmentioning
confidence: 99%